Size spectra of the edaphic fauna of typical Argiudol soils of the Rolling Pampa Region, Argentina - Víctor Velazco; Rosana Sandler; Maria Cynthia Valeria Sanabria; Liliana Falco; Carlos Coviella; Leonardo Saravia (Biodiversity Data Journal, 2023)
Soil-dwelling organisms populate the spaces—referred to as interstices—between the litter on the soil surface and the pores in the soil's organo-mineral matrix. These organisms have pivotal roles in soil ecosystem functions, such as the breakdown and decomposition of organic matter, the dispersal of bacterial and fungal spores and biological habitat transformation. These functions, in turn, contribute to broader ecosystem services like carbon and nutrient cycling, soil organic matter regulation and both chemical and physical soil fertility.This study provides morphological data pertaining to a range of soil organism sizes, specifically in Argiudol soils subjected to varying levels of agricultural activity in the Rolling Pampas Region, one of the world's most extensive and fertile plains.The primary focus is on soil microarthropods—namely, Acari (mites) and Collembola (springtails)—with a body width of less than 2 mm. These organisms constitute the majority of life in the intricate soil pore network. Additionally, the study documents species of earthworms (Oligochaeta, Crassiclitelata), recognised as ecosystem engineers for their ability to create physical channels in the soil matrix and to distribute organic matter. Moreover, the study includes measurements of morphological traits of soil-dwelling "macrofauna" (organisms with a body width greater than 2 mm), which are also implicated in various soil ecosystem functions. These include population regulation by apex predators, organic matter decomposition, biogenic structure formation, nutrient mobilisation and herbivory.In this paper, we report both the geographical locations and individual measurements of key morphological traits for over 7,000 specimens, covering a range of soil-dwelling organisms. These include springtails (Entognatha, Collembola), mites (Arachnida, Acari), earthworms (Oligochaeta, Crassiclitellata) and additional soil macrofauna. All specimens were collected from typical Argiudol soils located in three distinct agricultural systems characterised by varying levels of land-use intensity. To our knowledge, no other dataset exists providing this information for the Argentinian Pampas.